COVID-19 manifesting as syncope - Finsterer, Josef; MD , Fulvio A Scorza; MD , Carla A Scorza; MD , Ana C Fiorini (Jour Med Resh and Health Sci, 2021)
With interest we read the article by Canetta et al. about a study of 35 patients infected with SARS-CoV-2 who manifested initially with a syncope [1]. It was speculated that SARS-CoV-2 led to internalisation of angiotensin-converting enzyme-2 (ACE2) r